Жалоб много, но прибыль есть: злоупотребление сигнальнымиинститутами в российском ЖКХ - Litvintsev, Denis (Journal of Economic Sociology, 2023)
In 2022, a correspondence discussion on the challenges related to the functioning of the complaints institute within the housing and communal services sector in Russia was initiated within the pages of this journal. The discussion involved the author of this article and Olga Bessonova, a representative of the Novosibirsk School of Economics and Sociology. In response to the article titled “Complaints are not Gifts: Dysfunctionality of the Institution of Complaints in the Field of Housing and Communal Services ш Russia” (vol. 23, по 4, pp. 110—121), which critiques the effectiveness of the complaints institution from an interdisciplinary perspective, Prof. Bessonova published a response article titled “Ге Institutional Nature of Complaints in Market and Distributional Environments” (vol. 23, no 5, pp. 133—144). The aim of the present article 1 to continue the debate and broaden it to encompass a discussion of the issues related to the functioning of both signaling institutions (complaints and profit) in the context of the apartment building management market. The author provides a detailed commentary on the specifics of the methodology used to study problems in the housing sector, and conducts an analysis of several indicators from open sources that point to the existence of false complaints and, consequently, institutional abuses by apartment building owners. Concerning the institution of profit, the author presents common socio-economic practices related to profit manipulation by management companies, including strict budgeting, fictitious employment, and affiliations with contractors. These practices lead to the dysfunction of the profit institution. The primary conclusion of this article is that the institutional environment itself, along with legal and regulatory institutions, contribute to the dysfunction of signaling institutions. They do so by promoting and effectively endorsing abuses by all market participants in the absence of genuine competition, which is essential for the complaints system to function as feedback, in line with the approach of Janelle Barlow and Claus Moller.